2020
DOI: 10.1016/s2468-2667(20)30254-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of vision loss in China from 1990 to 2019: findings from the Global Burden of Disease Study 2019

Abstract: Background Vision loss is an important public health issue in China, but a detailed understanding of national and regional trends in its prevalence and causes, which could inform health policy, has not been available. This study aimed to assess the prevalence, causes, and regional distribution of vision impairment and blindness in China in 1990 and 2019.Methods Data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019 were used to estimate the prevalence of moderate and severe vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 33 publications
3
125
1
Order By: Relevance
“…The GBD 2019 study provided a comprehensive and up-to-date estimation of the epidemiology of diseases and injuries in different sexes and age groups, for 204 countries and territories, 21 regions, from 1990 to 2019 [12] . Details about the study design and methods of GBD studies have been extensively described in existing GBD literature [12] , [13] , [14] , [15] , [16] , [17] , [18] . Data of GBD studies are publicly available online, and can be extracted by Global Health Data Exchange query tool ( http://ghdx.healthdata.org/gbd-results-tool ).…”
Section: Methodsmentioning
confidence: 99%
“…The GBD 2019 study provided a comprehensive and up-to-date estimation of the epidemiology of diseases and injuries in different sexes and age groups, for 204 countries and territories, 21 regions, from 1990 to 2019 [12] . Details about the study design and methods of GBD studies have been extensively described in existing GBD literature [12] , [13] , [14] , [15] , [16] , [17] , [18] . Data of GBD studies are publicly available online, and can be extracted by Global Health Data Exchange query tool ( http://ghdx.healthdata.org/gbd-results-tool ).…”
Section: Methodsmentioning
confidence: 99%
“…Xu’s study has revealed that China’s vision loss burden had increased more rapidly than other G20 countries from 1990 to 2019 [ 18 ]. The main cause of moderate and severe visual impairment are uncorrected refraction disorders, cataract, and macular degeneration in 2019, which were the same in 1990.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of moderate and severe visual impairment are uncorrected refraction disorders, cataract, and macular degeneration in 2019, which were the same in 1990. Refraction disorders is the main cause of moderate visual impairment in people younger than 70 years [ 18 ]. Consist with these findings, refraction disorders are less affected by population aging than other eye diseases and the population affected are becoming younger.…”
Section: Discussionmentioning
confidence: 99%
“…A most recent survey on the causes of vision loss in China revealed that URE remains the major leading cause of moderate/severe vision impairment and blindness in China in the overall population (19,20). India and China account for approximately 50% of global vision impairment and blindness due to UREs (4,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of present URE may not be comparable with that derived from the population-based studies, especially when the different diagnostic criteria were used (29-36) (Table 5). Meanwhile, the impacts of URE in the Chinese adults were usually addressed when analyzing the cause of visual impairment (19,20,(37)(38)(39). Studies directly reporting the prevalence, distribution, and service coverage for URE among the adults in China are very limited.…”
Section: Discussionmentioning
confidence: 99%